ANALISIS YURIDIS PERBANDINGAN JUDICIAL PARDON DALAM UNDANG-UNDANG NO. 1 TAHUN 1946 TENTANG PERATURAN TENTANG HUKUM PIDANA DENGAN UNDANG-UNDANG NO. 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - KUSUMA, JAUHARI D.; LESTARI, B. FARHANA KURNIA; DEWI, JUNI PUSPITA (Ganec Swara, 2025)
With the enactment of Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code or the New Criminal Code, it has amended Law of the Republic of Indonesia Number 1 of 1946 concerning the Criminal Code. There have been several additions and updates to criminal law in Indonesia, especially regarding the formulation of the concept of Judicial Pardon. This study aims to determine the existence and significance of the concept of Judicial Pardon in the New Criminal Code and to determine the implications of its formulation. This type of research is normative research, which uses a statute approach, a conceptual approach, a comparative approach and a historical approach. The results of this study discuss the existence and significance of Judicial Pardon contained in Article 54 paragraph (2) of the New Criminal Code. The Old Criminal Code did not recognize Judicial Pardon and upheld the principle of legality where legal certainty is the strongest pillar, therefore judges have no other legal options in deciding cases. The formulation of the principle of Judicial Pardon in the New Criminal Code in its implementation in the future is very good, because it provides broad benefits to the perpetrators and to the community as well. However, the formulation of the New Criminal Code does not provide definite limitations or criteria related to the requirements of Judicial Pardon which can later lead to multiple interpretations among judges in implementing the concept